Assessing self-study manual on students' academic achievement in UiTM Penang Branch Campus / Jamilah Karim, Peridah Bahari and Norhayati Mohammad Noor - Karim, Jamilah; Bahari, Peridah; Mohammad Noor, Norhayati (Universiti Teknologi MARA Cawangan Pulau Pinang, 2003)
Even for a person who has been teaching 10 to 15 years, the urge to keep on improving teaching technique will always be one prior agenda on the educators' mind. The purpose of this article is to determine the effectiveness of using student self- study manual as instructional material for UiTM Penang Engineering students. The academic performance from two different groups of students was analyzed to see whether there is any improvement in students' performance when self-study manual was used in the classroom. Sample (students) taken was from various engineering programmes and was formed into two different academic years. This paper will look into the difference of percentage for passes and failures and conclude whether the use of self-study manual will be a help to students and lecturers.